The Practical Impact of Ontologies on Biomedical Informatics - Cimino, J. J.; Zhu, X. (Yearbook of Medical Informatics, 2006)
To examine recent research work in the development and evaluation of controlled biomedical terminologies – especially, the representation of structured, controlled definitional knowledge about the terms themselves; such terminologies are often referred to as “ontologies”.A review of the published literature using PubMed, as well as full-text searches of recent Medinfo and American Medical Informatics Association (AMIA) Symposia proceedings, searching for the terms “ontology” and “ontologies” and for articles discussing specific, prominent ontological work.We summaries the ontologic aspects of twelve current terminology projects: Galen, the Unified Medical Language System (UMLS), the Medical Entities Dictionary (MED), SNOMED-CT, LOINC, the Foundational Model of Anatomy (FMA), the Gene Ontology (GO), ISO Reference Terminology Model for Nursing Diagnosis, NDF-RT, RxNorm, the NCI Thesaurus, and DOLCE+. We discuss the origins, domain, and ontologic representation of each of these and attempt to summarize the impact that each has had on terminologic work and biomedical applications. We also note the contributions of the Protégé tool to many of these efforts.Terminologic research and development have advanced significantly in the past 20 years, especially since the recent orientation toward controlled biomedical ontologies. This work has had significant impact on the development of terminologies themselves, their acceptance and dissemination as standards, and their use in supporting biomedical information systems.
Keywords: Controlled Terminology; Ontology; Unified Medical Language System